Assessing Composite Livelihood Security and its Determinants Among Rural Households (Indian Journal of Extension Education, 2023)
The study was conducted during 2022 in Lucknow district of Uttar Pradesh to analyze the livelihood security of rural households. Data was collected from 515 households through personal interview method using kobo collect. Landless and marginal farmers were more food insecure in the region. Forty four % of the households were food insecure. Composite livelihood security index was constructed using six domain indicators viz., habitat, health, economic, food, nutrition and social participation security. The weight for each domain indicator was derived from principal component analysis. The composite livelihood security index was 0.44 among the respondents. The livelihood security was high for medium farmers (0.46) followed by small farmers (0.45). Farming experience, social participation, livestock possession, income, calorie intake, body mass index and wealth significantly influenced the livelihood security. Lack of awareness on pest and disease control and poor price realization were the major constraints faced by the farmers. Technological, institutional and policy interventions are necessary to enhance their livelihood status.